Penerapan Etika Bisnis Islam Dalam Transaksi Jual Beli Sembako Di Pasar Kedurus Surabaya - Syahputri, Tyas Fariha; Suryaningsih , Sri Abidah (Jurnal Ekonomika dan Bisnis Islam, 2022)
The high market demand for necessities has increased their business, but many of them do not fully understand islamic business ethics in buying and selling transactions. The purpose of this research is to identify and analyze the application of islamic business ethics in the purchase and sale of necessities at the Kedurus Market in Surabaya City. The descriptive qualitative method was used in the research. The techniques used to collect research data include observation, interviews, and documentation. According to the findings of this study, the application of islamic business ethics in buying and selling groceries at Kedurus Market only applies and carries out four principles of islamic business ethics, namely unity, balance, free will, and responsibility. The application of truth or honesty principle has not been applied by basic food traders because they do not explain the honesty of the quality of goods to buyers during trading. However, purchasing and selling transactions have been carried out by the pillars of purchasing and selling, as well as the form of purchasing ande selling used by food traders, namely ba’i an-naqd, ba’i salam, ba’i ajal, and ba’i musawamah. And the most common khiyar is khiyar majlis and khiyar aib.